Технико-экономическое обоснование ферментации куриного помета для разведения земляных червей: обзор - Ли, Я.; Лемешевский, В. О.; Максимова, С. Л. (БНТУ, 2023)
Conventional methods of agriculture and waste management are plagued with environmental problems and resource wastage, so there is an urgent need to find more sustainable solutions. The technology of vermiculture of earthworms from fermented chicken manure has attracted much attention in the field of agriculture and waste management. The present study aims to delve into the feasibility of this novel approach by examining in detail the advantages and possible challenges of the technology, as well as its prospects for sustainable agriculture and organic fertilizer production, through an extensive and comprehensive analysis of relevant literature.